"As a Trans Person You Don't Live. You Merely Try to Survive and Apologize Every Day for Who You Are" – Discrimination Experiences Among Trans Individuals in Greece". Issue 7 (7th June 2023) - Papadaki, Vasileia; Ntiken, Andreas
ABSTRACT: This qualitative study sheds light on an issue very little research has been conducted on so far, the discrimination trans people in Greece are subjected to every day. The findings presented in this paper are part of a larger study focusing on trans persons' life experiences in contemporary Greece. Eleven participants identified various discrimination areas, employment, education, family, romantic relationships and daily life; participants also pointed out specific measures that would contribute to the improvement of their life. Findings are discussed in relation to measures toward eliminating discrimination against trans persons such as the improvement of gender recognition legislation, an increase in general education regarding gender identity issues and the need for transgender-focused research.